How accurate and effective are screening tools and subsequent interventions for intimate partner violence in non-high-risk settings (IPV)? A rapid review. Issue 4 (16th August 2021) - Ali, Parveen; Allmark, Peter; Booth, Andrew; McGarry, Julie; Woods, Helen B.; Seedat, Farah
Abstract : Purpose: The purpose of this paper is to estimate the accuracy and effectiveness of screening tools and subsequent interventions in the detection and treatment of intimate partner violence (IPV) in non-high-risk settings (defined here as those in which routine IPV screening does not take place in the UK, such as in general practice). Design/methodology/approach: Rapid review as defined by Grant and Booth – it is used under time or financial constraint to assess what is known using systematic review methods. Medline, PsycINFO, Embase and Cochrane Library databases to May 2019 were searched for "intimate partner violence" and synonyms plus terms related to screening and interventions. A Medline update was performed in August 2020. Data were extracted with the help of a predesigned tool and were synthesised to answer the two study aims. Data were mixed quantitative and qualitative. Findings: The search yielded 10 relevant papers on screening (6 on accuracy and 4 on effectiveness) and 13 on intervention. These showed evidence of the effectiveness of simple screening tools and of subsequent interventions. However, the evidence was insufficient to support a change in UK guidelines which currently do not recommend their use outside of current high-risk environments. Originality/value: Clinicians outside of high-risk areas should consider the use of some IPV screening tools and interventions but only within research protocols to gather further evidence.